Toward a Focused Conceptualization of Collateral Consequences Among Individuals Who Sexually Offend: A Systematic Review. (February 2022) - Hamilton, Emma
Despite speculation regarding the role of collateral consequences of sexual offender policies in psychosocial and criminogenic outcomes, there has been no empirical analysis in the extant literature examining these links. Lack of conceptual underpinnings and no psychometrically valid measure of collateral consequences has limited study in this area. A systematic literature review was conducted to assess the state of measurement in terms of conceptual and operational definitions, populations sampled, domains assessed, items used, and scale properties reported. Nineteen studies met inclusion criteria. Themes emerged regarding commonly assessed collateral consequences, the misconnect between legal and psychological conceptualizations of collateral consequences, the division between external (i.e., social) and internal (i.e., affective) collateral consequences, as well as a trend toward emphasizing the psychological damages (in addition to discrete experiences of loss) associated with a sexual offense. Findings are discussed, and a unifying definition of collateral consequences is proposed to guide future scale development.